Non-stress test as an admission test to assess the outcome in all pregnant women attending tertiary care center - D., Rita; B., Sirisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Perinatal mortality remains high in developing countries, including India, where it is approximately 32 per 1000 live births. The non-stress test (NST) is a non-invasive, simple, and widely used method to assess fetal well-being after 30 weeks of gestation. A reactive NST usually indicates adequate fetal oxygenation, while a non-reactive result may suggest hypoxia or neurological depression. Methods: This prospective study included 100 pregnant women (>30 weeks gestation) with singleton pregnancies admitted to the labour ward of Navodaya medical college, Raichur. NST was performed in the semi-recumbent or left lateral position for 20 minutes (extended to 40 minutes if non-reactive). Outcomes assessed included mode of delivery, birth weight, Apgar scores at 1 and 5 minutes, NICU admissions, maternal complications, and hospital stay duration. Results: Reactive NST was recorded in 78% of participants, non-reactive in 16%, and suspicious in 6%. Non-reactive and suspicious NSTs were significantly associated with higher emergency caesarean section rates (50% vs 17.9%), increased NICU admissions (37.5% and 33.3% vs 5.1%), lower Apgar scores, and greater incidence of meconium-stained liquor and intrapartum fetal distress (p<0.05). Conclusions: Admission NST is a reliable predictor of perinatal outcome. Reactive NSTs are associated with favorable outcomes, whereas non-reactive/suspicious results indicate higher perinatal risk, necessitating timely intervention.